Antimicrobial activity of Callistemon citrinus and Callistemon salignus methanolic extracts - Cock, I.E. (Pharmacognosy Communications)
Introduction: Australian Callistemon species had a role as traditional bush medicine for Australian Aborigines, including use as an antiseptic agent. Despite this ethnobotanical usage, the antimicrobial properties of Callistemon spp. have not been rigorously studied. Methods: The antimicrobial activity of methanolic extracts of Callistemon citrinus and Callistemon salignus were investigated by disc diffusion and growth time course assays against a panel of bacteria and fungi. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: C. citrinus leaf extracts inhibited the growth of 43% and flower extracts inhibited the growth of 64% of the bacteria tested, respectively. Gram-positive bacteria (100% inhibited) were more susceptible to C. citrinus extracts than were Gram-negative bacteria (27% inhibited by leaf extracts; 55% inhibited by flower extracts). In comparison, C. salignus leaf extract inhibited the growth of 29% of the bacteria tested compared with 43% inhibited for the flower extract. Gram-positive bacteria (100% inhibited) were more susceptible to C. salignus leaf extract than were Gram-negative bacteria (9% inhibited). Similar results (27% Gram-negative bacteria inhibited and 100% Gram-positive bacterial inhibition) were also seen for C. salignus flower extract. Very little antifungal activity was seen for any extract with only C. albicans being inhibited by C. salignus leaf extract. The antibacterial activity of the C. citrinus and C. salignus flower extracts was further investigated by growth time course assays. These extracts showed significant growth inhibition activity in cultures of Bacillus cereus, Aeromonas hydrophilia, Pseudomonas fluorescens and Bacillus subtilis within 1 hour. All extracts displayed low toxicity in the Artemia franciscana nauplii bioassay. Conclusions: The low toxicity of these Callistemon extracts and their inhibitory bioactivity against a panel of bacteria validates Australian Aboriginal usage of Callistemon citrinus and Callistemon salignus as antiseptic agents and confirms their medicinal potential.
Keywords: Callistemon citrinus; Callistemon salignus; Australian plants; antibacterial activity; medicinal plants; toxicity